Freshwater fish diversity and composition in Batang Kerang floodplain, Balai Ringin, Sarawak - Abdul Rahim, Khairul Adha; Daud, Siti Khalijah; Siraj, Siti Shapor; Arshad, Aziz; Esa, Yuzine; Ibrahim, Eza Rena (Universiti Putra Malaysia Press, 2009)
The diversity and composition of fish communities in brown and black water habitats at Batang Kerang in Balai Ringin, Sarawak, were evaluated during high and low water seasons. A total of 234 individual fish representing 36 species belonging to 13 families were captured. The fish communities in both the habitats were apparently from 32 species belonging to 12 families in brown water, and only 12 species from 7 families in the black water habitats. The fish fauna in the brown water was dominated by the Cyprinidae (63.8%) family, while the Helostomatidae (59.8%) family dominated the black water habitat. Various water parameters, such as dissolved oxygen, pH values, conductivity and water transparency, total suspended solid (TSS) and ammonium-nitrogen concentrations were significantly different (p<0.05) between the black and brown water habitats. The brown water habitat supports more diverse and abundant populations of freshwater fishes than the black water habitat. However, introduced species such as H. temmincki and the increase of commercial fishing may also have affected the population of native fish.